Hypochlorite‐Mediated Modulation of Photoinduced Electron Transfer in a Phenothiazine–Boron dipyrromethene Electron Donor–Acceptor Dyad: A Highly Water Soluble "Turn‐On" Fluorescent Probe for Hypochlorite. Issue 12 (18th May 2018) - Soni, Disha; Duvva, Naresh; Badgurjar, Deepak; Roy, Tapta Kanchan; Nimesh, Surendra; Arya, Geeta; Giribabu, Lingamallu; Chitta, Raghu
Abstract: A highly water‐soluble phenothiazine (PTZ)–boron dipyrromethene (BODIPY)‐based electron donor–acceptor dyad (WS‐Probe ), which contains BODIPY as the signaling antennae and PTZ as the OCl − reactive group, was designed and used as a fluorescent chemosensor for the detection of OCl − . Upon addition of incremental amounts of NaOCl, the quenched fluorescence ofWS‐Probe was enhanced drastically, which indicated the inhibition of reductive photoinduced electron transfer (PET) from PTZ to 1 BODIPY*; the detection limit was calculated to be 26.7 nm . Selectivity studies with various reactive oxygen species, cations, and anions revealed thatWS‐Probe was able to detect OCl − selectively. Steady‐state fluorescence studies performed at varied pH suggested thatWS‐Probe can detect NaOCl and exhibits maximum fluorescence in the pH range of 7 to 8, similar to physiological conditions. ESI‐MS analysis and 1 H NMR spectroscopy titrations showed the formation of sulfoxide as the major oxidized product upon addition of hypochlorite. More interestingly, whenWS‐Probe was treated with real water samples, the fluorescence response was clearly visible with tap water and disinfectant, which indicated the presence of OCl − in these samples. The in vitro cell viability assay performed with human embryonic kidney 293 (HEK 293) cells suggested thatWS‐probe is non‐toxic up to 10 μm and implicates the use of the probe for biological applications. Abstract : A highly water‐soluble phenothiazine–boron dipyrromethene dyad (WS‐Probe ) was synthesized (see figure) and used as a photoinduced electron transfer (PET)‐based "turn‐on" fluorescent chemosensor for the sensitive and selective detection of hypochlorite. On addition of OCl −, the fluorescence ofWS‐Probe was enhanced by sevenfold and a detection limit of 26.7 nm was found. The use ofWS‐Probe for the detection of OCl − in real samples was explored.